Examining The Relationship Between AI-Based Language Learning Engagement and Grammar Achievement: Evidence From Duolingo Use - Ghafur, Abdul; Rahmawati, Fithriyah; Baidawi, Achmad (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
Nowadays, the usage of AI-based language learning applications has been increasing over time, where students are able to learn any languages easily anytime and anywhere. This such phenomenon raised some questions related to its usage duration (screen time) alongside the learners’ grammatical competence. Therefore, this research aimed to explore and examine the relationship between students’ screen time of an AI-based language learning app, namely Duolingo, and their grammar achievement. This research was conducted using a quantitative, non-experimental design. The data were analyzed on IBM SPSS Statistics, including descriptive analysis, normality test, and Spearman rank-order correlation. The correlation coefficient (ρ) at 0.061 and the p-value at 0.749, with the set of significance level at alpha (α) 0.05. Those results revealed an extremely weak and not statistically significant relationship between Duolingo screen time and grammar achievement. Furthermore, these findings suggest that the duration of learning on Duolingo alone may not be strongly enough associated with their grammar competence. Alongside these findings, the authors would like to emphasize the importance of learning quality over the duration of usage itself.